Diet of Sigmodontine rodents (Cricetidae) in tropical montane forests from Huánuco, Peru - Noblecilla, Maggie C. (2012)
We analyzed the stomach contents of five species of sigmodontine rodents: Akodon orophilus, Microryzomys altissimus, M. minutus, Thomasomys notatus, and T. kalinowskii, from mountain forests of Huánuco, Perú (2564 - 3850 m). We found that A. orophilusis an insectivorous species because the high volume of arthropods (adults and larvae) in the stomach contents (90.1%); T. notatusand T. kalinowskiiare primarily herbivorous because they had a high volume of plant material of 89% and 67.75% respectively; whereas M. altissimusand M. minutusare omnivorous because they presented similar volume percentages for plants and arthropods. T. kalinowskiiis considered a generalist species because it had the highest niche breadth (4.61), whereas A. orophilusis considered a specialist because it had the lowest value (1.70). Akodon orophilusregistered a low coefficient of variation (CV= 20%) showing a preference for consuming adult arthropod, and also a significatively high consumption of arthropod larvae in the wet season, being the only species with a seasonal variation in the diet. On the other hand, the niche overlap was less than 0.75 in 80% of species pairs indicating low similarity in the diet, but greater than 0.75 between M. altissimus -T. notatus(0.822) and M. minutus -T. kalinowskii(0.816) suggesting a higher diet similarity. We conclude that these sigmodontine rodents, sympatric in the montane forests of Huánuco, exhibit dissimilar diets, probably as a strategy to prevent or lessen interspecific competition.